COPPER(II) SORPTION ONTO GOETHITE, HEMATITE AND LEPIDOCROCITE: A SURFACE COMPLEXATION MODEL BASED ON AB INITIO MOLECULAR GEOMETRIES AND EXAFS SPECTROSCOPY - Peacock C.L.; Sherman D.M. (My University, 2004)
We measured the adsorption of Cu(II) onto goethite (α-FeOOH), hematite (α-Fe2O3) and lepidocrocite (γ-FeOOH) from pH 2–7. EXAFS spectra show that Cu(II) adsorbs as (CuO4Hn)n−6 and binuclear (Cu2O6Hn)n−8 complexes. These form inner-sphere complexes with the iron (hydr)oxide surfaces by corner-sharing with two or three edge-sharing Fe(O,OH)6 polyhedra. Our interpretation of the EXAFS data is supported by ab initio (density functional theory) geometries of analogue Fe2(OH)2(H2O)8Cu(OH)4and Fe3(OH)4(H2O)10Cu2(OH)6 clusters. We find no evidence for surface complexes resulting from either monodentate corner-sharing or bidentate edge-sharing between (CuO4Hn)n−6 and Fe(O,OH)6 polyhedra. Sorption isotherms and EXAFS spectra show that surface precipitates have not formed even though we are supersaturated with respect to CuO and Cu(OH)2. Having identified the bidentate (FeOH)2Cu(OH)20 and tridentate (Fe3O(OH)2)Cu2(OH)30 surface complexes, we are able to fit the experimental copper(II) adsorption data to the reactions 3(FeOH)+2Cu2++3H2O=(Fe3O(OH)2)Cu2(OH)30+4H+ and 2(FeOH)+Cu2++2H2O=(FeOH)2Cu(OH)20+2H+. The two stability constants are similar for the three iron (hydr)oxide phases investigated.